Chest x-ray findings in tuberculosis patients identified by passive and active case finding: A retrospective study. (February 2019) - Rastoder, Ema; Shaker, Saher Burhan; Naqibullah, Matiullah; Wille, Mathilde Marie Winkler; Lund, Mette; Wilcke, Jon Torgny; Seersholm, Niels; Jensen, Sidse Graff
Abstract: Background: Chest x-ray is central in screening and diagnosis of tuberculosis. However, sputum culture remains gold standard for diagnosis. Aim: To establish the rate of normal chest x-rays in tuberculosis patients found by spot sputum culture screening, and compare them to a group identified through passive case finding. Method: Chest x-rays from 39 culture-positive patients, identified by spot sputum culture screening in Copenhagen from 2012 to 2014, were included in the study (spot sputum culture group(SSC)). 39 normal chest x-rays from persons screened by mobile x-ray, and 39 chest x-rays from tuberculosis-patients identified through passive case finding(PCF) were anonymised and randomised. Two respiratory physicians and two radiologists assessed the chest x-rays. Results: The normal chest x-ray rate was higher in the non-tuberculosis control group (median = 32 (82.1%), range = 74.4% – 100%), compared to the SSC group (median = 7 (17.9%), range = 10.3% – 33.3%), and the PCF controls (median = 3(7.7%), range = 2.6% – 15.4%). In the SSC group 14 (35.9%) were categorized as normal by at least one study participant. Conclusion: A substantial minority of patients diagnosed with tuberculosis by spot sputum culture screening, and through passive case finding would not have been identified with chest x-ray alone, highlighting that a normal chest x-ray does not exclude pulmonary tuberculosis.